Sunnah-Syiah bergandengan tangan! mungkinkah? : kajian atas konsep ajaran dan pemikiran - Shihab, Moh. Quraish (Ciputat, Tangerang : Lentera Hati, 2007)
Concepts of shia and sunni teachings and the possibilities to unite them towards on belief
Includes bibliographical references (p. 287-293) and index
Kepustakaan : p. 287-293
Keywords: Islam -- Indonesia; Shi'ah -- Relations -- Sunnites; Sunnites -- Relations -- Shi'ah; Islamic sects -- Indonesia